Proyecto de factibilidad para la implementación de una empresa de Producción de harina de colocasia esculenta papa china y su comercialización en la ciudad de Loja. - GALLARDO, YANETH DE JESÚS (2010)
The investigation work refers to the industrialization and commercialization of Colocasia Esculenta (Chinese Pope) in the city of Loja, for the depreciation of the production costs, since in the canton Palanda of Zamora's county Chinchipe, the matter exists it prevails required and in the city of Loja, the necessary manpower. To discover the feasibility of the project, he/she was carried out the corresponding market study, size and localization, engineering of the project, financial evaluation and the organization of the company industrializadora and comercializadora of colocasia esculenta (Chinese Pope). In the market study you could determine that an effective demand exists for the first year of activity of the company of 642.490 pounds of flour of colocasia esculenta, enough to implement the industrial plant in the city of Loja. After having carried out the financial evaluation, with their respective indexes, as the Current Net Value with a value of 13490.03 dollars, an Internal Rate of Return of the one 23.10%, the Relationship Benefits Cost of 1.09, the Period of Recovery of Capital 4 years old, 4 months and 9 days, they give positive indicators as a result, which assure us that it can be carried out this project without more difficulties. One of the financial indicators that demonstrates that the project is profitable is TIR that gives us a much higher percentage that the opportunity cost that has capital in the local market, for such a reason makes sure that the project is executable. Their administrative organization has also settled down with the hierarchical different levels and with the functions that it should carry out each one of people that you/they will lend services in the company. This as such, it is structured and it has been foreseen that the lifespan of the project is of a ten year-old period, being located in the city and county of Loja.